ANALISIS KEPUASAN PELAYANAN PASIEN PADA INSTALASI RAWAT JALAN DI RUMAH SAKIT RUMAH SAKIT UMUM DAERAH EMBUNG FATIMAH BATAM DENGAN PENDEKATAN LEAN SERVICE DAN SERVICE PERFOMANCE - Adhitomo Wirawan; Venia Yunita (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2017)
The aim of this research is useful to know the satisfaction of outpatient at Rumah Sakit Embung Fatimah Batam. Service satisfaction is the end result perceived by the user of the product or service, whether it is less, equal or exceeds the desired expectations. By using lean sear vice pedekantan and service performance. This study resulted in five indicators of service quality at Rumah Sakit Embung Fatimah Batam which is included in quadrant I group which is the main priority to be improved to exceed patient expectation. The five indicators are: adequate waiting room facilities (2.5), waiting room environment and good lighting (77,50), accessible information access (2,9), service to patient complaints done quickly and responsive (2 , 9), the officer receives advice from the patient (2.9).